2014
DOI: 10.1038/ncomms4042
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying interface and bulk contributions to spin–orbit torque in magnetic bilayers

Abstract: Spin-orbit interaction-driven phenomena such as the spin Hall and Rashba effect in ferromagnetic/heavy metal bilayers enables efficient manipulation of the magnetization via electric current. However, the underlying mechanism for the spin-orbit interaction-driven phenomena remains unsettled. Here we develop a sensitive spin-orbit torque magnetometer based on the magneto-optic Kerr effect that measures the spin-orbit torque vectors for cobalt iron boron/platinum bilayers over a wide thickness range. We observe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
252
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(264 citation statements)
references
References 30 publications
9
252
1
2
Order By: Relevance
“…It was also recently demonstrated that both collinear [38] and non-collinear AFMs [33,[39][40][41][42] can generate a large SOT on FMs in AFM/FM heterostructures. While the origin of such a torque is not clear [41] it is known that in heavy metal/FM heterostructures, the SHE plays an important role [43,44]. Here we show, that apart from the conventional SHE, which was theoretically studied in Ref.…”
mentioning
confidence: 46%
“…It was also recently demonstrated that both collinear [38] and non-collinear AFMs [33,[39][40][41][42] can generate a large SOT on FMs in AFM/FM heterostructures. While the origin of such a torque is not clear [41] it is known that in heavy metal/FM heterostructures, the SHE plays an important role [43,44]. Here we show, that apart from the conventional SHE, which was theoretically studied in Ref.…”
mentioning
confidence: 46%
“…1(b)). Second order PHE measurements were carried out to quantify the spin current induced effective field in both FeMn/Pt bilayers and NiFe/FeMn/Pt trilayers 10,12 the schematic of Fig. 2(a), when a charge current j c flows in x-direction, a spin current j s is generated In addition to Hall bars, coupon films have also been prepared for X-ray diffraction and magnetic measurements.…”
Section: Methodsmentioning
confidence: 99%
“…7(a). For a better linear approximation, the data at low fields were excluded and only the data at fields above ±1 kOe were used for the fitting 10 . H I can be calculated from the slope k by using the relation H I = 2kH bias .…”
Section: Phe Measurements Of Femn/pt Bilayersmentioning
confidence: 99%
See 1 more Smart Citation
“…Values of DL j ξ for Pt have been reported spanning the range 0.06 -0.12 [19,[27][28][29], depending on the FM/Pt interface [31], and are usually accompanied by a relatively small field-like (FL) torque efficiency whose magnitude and sign vary with the interface, FM magnetic anisotropy and temperature [29,[32][33][34][35][36]. From an analysis of SBF based on a spin diffusion model [24,25] is a well-known phenomenon due to strong diffusive scattering at a Pt surface [48,[53][54][55][56][57].…”
mentioning
confidence: 99%